Reaction of Benzaldehyde Hydrazones with 2-Diazo-1,2-diphenylethanone - Singh, G.S. (Asian Journal of Chemistry, 2010)
An equimolar reaction of benzaldehyde hydrazones with 2-diazo- 1,2-diphenylethanone affords benzaldehyde N-diphenylacyl hydrazones as a result of reaction of diphenyl ketene, generated in situ from the thermal decomposition of 2-diazo-1,2-diphenylethanone, with NH2 of hydrazones.